Gertrude Stein: A Physician Who Wasn’t to Be - James B. Young (Methodist DeBakey Cardiovascular Journal)
After a tumultuous time in the United States, including flunking out of medical school in 1901, Gertrude Stein, an iconic American author, art lover, and critic, moved to Paris in 1903 as an avant garde modernist who became a leading and legendary guru in the Parisian art and literature world.